Audiovisual Content as a Marketing Strategy. Branded content: Caso de Eugenio Recuenco - Gómez Arroyo, Ana Rosa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Communication society is involved in a digital evolution process. The creation of contents for the Internet is part of digital culture and thus advertising has adapted its formats to this new paradigm. This study attempts to show the relevance of Branded Content strategy. Audiovisual content is analysed through a qualitative research methodology. Digital space transformation, connexion and integration of communication channels, and emotional connexion will be discussed. In conclusion, Branded Content is one of the most suitable strategies to convey brand identity to consumers through different formats.